Asymptomatic and Symptomatic Carotid Stenosis: An Obsolete Classification?. (23rd January 2012) - Chatzikonstantinou, Anastasios; Wolf, Marc E.; Schaefer, Anke; Hennerici, Michael G.
Abstract : Since many years, clinical decisions about the management of patients with carotid stenosis have been based on the distinction between "asymptomatic" and "symptomatic" presentations. This was also reflected by the design of previous studies on the surgical versus conservative treatment and of current studies on interventional treatment versus surgery. Both terms, however, only address different phases of activity of the one and the same condition and blur the significant message that carotid stenosis is a most important marker of systemic atherosclerosis, which is accompanied by a much higher risk of cardiovascular events rather than stroke. As a consequence, early diagnosis and followup during best medical treatment, life-style management, regular cardiovascular assessment, and good control of all vascular risk factors should be recommended in all patients with carotid stenosis—whether identified in the long-lasting "silent" or short-lasting "vulnerable" period lasting only a few weeks after cerebral ischemia. Patients in this short time window benefit from additional carotid intervention, under the condition of an individually favorable benefit-risk ratio ("individual vulnerability").